Conversations about FGM in primary care: a realist review on how, why and under what circumstances FGM is discussed in general practice consultations - Sue Ziebland; Chrysanthi Papoutsi; Claire Duddy; Gabrielle Harrison (BMJ Open)
Objectives Little is known about the management of female genital mutilation (FGM) in primary care. There have been significant recent statutory changes relevant to general practitioners (GPs) in England, including a mandatory reporting duty. We undertook a realist synthesis to explore what influences how and when GPs discuss FGM with their patients.Setting Primary care in England.Data sources Realist literature synthesis searching 10 databases with terms: GPs, primary care, obstetrics, gynaecology, midwifery and FGM (UK and worldwide). Citation chasing was used, and relevant grey literature was included, including searching FGM advocacy organisation websites for relevant data. Other potentially relevant literature fields were searched for evidence to inform programme theory development. We included all study designs and papers that presented evidence about factors potentially relevant to considering how, why and in what circumstances GPs feel able to discuss FGM with their patients.Primary outcome measure This realist review developed programme theory, tested against existing evidence, on what influences GPs actions and reactions to FGM in primary care consultations and where, when and why these influences are activated.Results 124 documents were included in the synthesis. Our analysis found that GPs need knowledge and training to help them support their patients with FGM, including who may be affected, what needs they may have and how to talk sensitively about FGM. Access to specialist services and guidance may help them with this role. Reporting requirements may complicate these conversations.Conclusions There is a pressing need to develop (and evaluate) training to help GPs meet FGM-affected communities’ health needs and to promote the accessibility of primary care. Education and resources should be developed in partnership with community members. The impact of the mandatory reporting requirement and the Enhanced Dataset on healthcare interactions in primary care warrants evaluation.PROSPERO registration number CRD42018091996.